English Language Acquisition Through Technology-Based Learning: A Review Of Motivation, Learner Autonomy, And Self-Efficacy Of Senior High School Students - Ambarita, Dharmawati; Susyla, Dian (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study presents a literature-based review of Indonesian journal articles and academic books published within the last five years that examine English language acquisition through technology-based learning, with particular emphasis on motivation, learner autonomy, and self-efficacy among senior high school students. The review is grounded in the increasing integration of digital technologies in English language teaching in Indonesia, driven by national education policies and the demands of globalization. Although numerous studies have explored technology-enhanced English learning, existing research in the Indonesian EFL context largely examines psychological variables in isolation, resulting in fragmented theoretical and pedagogical insights. Using a library research approach, this study systematically analyzes peer-reviewed journals, scholarly books, and policy documents through content analysis techniques. The findings indicate that technology-based learning can effectively support English language acquisition when accompanied by strong learner motivation, well-developed autonomy, and positive self-efficacy beliefs. These three factors are shown to interact dynamically, shaping students’ engagement, persistence, and ability to utilize digital learning affordances meaningfully. However, the review also reveals persistent challenges, including teacher-centered instructional practices, uneven development of learner autonomy, and limited pedagogical scaffolding in digital environments. This study concludes that technology integration alone is insufficient to enhance English proficiency without deliberate attention to learners’ psychological readiness. The synthesis contributes theoretically by reinforcing socio-cognitive and constructivist perspectives on language learning and practically by offering insights for teachers, curriculum developers, and policymakers to design learner-centered, psychologically informed, and sustainable technology-enhanced English learning environments in Indonesian senior high schools.